2020
DOI: 10.1097/md.0000000000019358
|View full text |Cite
|
Sign up to set email alerts
|

Is intravenous thrombolysis safe for acute ischemic stroke patients taking warfarin with INR 1.9?

Abstract: Introduction: Intravenous thrombolysis is not suitable for patients undergoing oral anticoagulants therapy, with INR > 1.7 or PT > 15 s. We described a case of intravenous thrombolysis in a patient with INR 1.9. Patient concerns: A 66-year-old female patient was diagnosed with acute appendicitis complicated with atrial fibrillation. Seven days after admission, the patient suffered mixed aphasia with right limb asthenia. The NIHSS score was 11 points. and early infarctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A large cross-sectional study [8] found that the prognosis of patients with an INR > 1.7 was the same as that of the other patients. Two cases have successfully reported the use of IVT in patients presenting with AIS and an INR of 1.9 (the INR was not as high as our case, and PT and detailed changes of blood coagulation function were not mentioned) [9,10]. Thus, IVT with rt-PA may not increase the risk of symptomatic intracranial hemorrhage (sICH) or poor prognosis in warfarin-treated stroke patients with an INR > 1.7.…”
mentioning
confidence: 55%
“…A large cross-sectional study [8] found that the prognosis of patients with an INR > 1.7 was the same as that of the other patients. Two cases have successfully reported the use of IVT in patients presenting with AIS and an INR of 1.9 (the INR was not as high as our case, and PT and detailed changes of blood coagulation function were not mentioned) [9,10]. Thus, IVT with rt-PA may not increase the risk of symptomatic intracranial hemorrhage (sICH) or poor prognosis in warfarin-treated stroke patients with an INR > 1.7.…”
mentioning
confidence: 55%